2017
DOI: 10.1039/c7cp04006g
|View full text |Cite
|
Sign up to set email alerts
|

Concerted transfer of multiple protons in acid–water clusters: [(HCl)(H2O)]2 and [(HF)(H2O)]4

Abstract: Molecular dynamics simulations using directly ab initio potentials are carried out for the ionically bonded clusters [(Cl)(HO)] and [(F)(HO)] to explore their transitions to the hydrogen-bonded [(HCl)(HO)] and [(HF)(HO)] structures during the first picosecond of simulation. Both the ionic and the H-bonded structures that are formed are highly symmetric. It is found that proton transfers are concerted in all trajectories for [(Cl)(HO)]. For [(F)(HO)], the fully concerted mechanism is dominant but partially conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Cooperativity has been reported as an important effect in studies about acid ionization and hydration of ions (Tielrooij et al, 2010;Zakai et al, 2017). But even when cooperativity is one of those concepts that seems intuitively clear, it is not rigorously defined.…”
Section: Cooperativitymentioning
confidence: 99%
See 1 more Smart Citation
“…Cooperativity has been reported as an important effect in studies about acid ionization and hydration of ions (Tielrooij et al, 2010;Zakai et al, 2017). But even when cooperativity is one of those concepts that seems intuitively clear, it is not rigorously defined.…”
Section: Cooperativitymentioning
confidence: 99%
“…Recently, Zakai et al performed classical molecular dynamics simulations to illustrate the transitions between the H-bonded and ionic isomers of (HCl)2(H2O)2 (Figure 1b and 1c) and of (HF)4(H2O)4 (Zakai et al, 2017). They reported that proton transfers were fully concerted in all trajectories for [Cl -⋯H3O + ]2, whereas for [F -H3O + ]4, the fully concerted 5 mechanism is dominant but partially concerted transfers of two or three protons at the same time also occur.…”
Section: Introductionmentioning
confidence: 99%
“…performed classical molecular dynamics simulations to illustrate the transitions between the H‐bonded (Figure 1b) and ionic (Figure 1c) isomers of (HCl) 2 (H 2 O) 2 and (HF) 4 (H 2 O) 4. [26] They found that proton transfers were fully concerted in all trajectories for [Cl − ⋯H 3 O + ] 2 , while for [F − H 3 O + ] 4 , the fully concerted mechanism is dominant, but two or three proton transfers also occur at the same time. The authors remarked that the high symmetry of the ionic and the H‐bonded structures plays a crucial role in the collective proton propagation and cooperative effects.…”
Section: Introductionmentioning
confidence: 99%
“…For example, AIMD simulations by Hassanali et al , showed that when the water wire was “polarized” by a pair of hydronium and hydroxide ions approaching each other at 4–8 Å, one found a concerted motion of several protons along the water wire between the ion pair. Of course, the ion pair is not limited to hydronium and hydroxide as other AIMD simulations also identified concerted pathways for proton transfer between water-separated acid–base pairs, for example, between carboxylic and phenolic acids (one of which is deprotonated) by Thomas and co-workers and between hydronium and halides by Zakai et al A more recent study of a hydrated excess proton in bulk water by the Voth group proposed that while concerted events occur, the majority of proton movements are rattling motions, where the excess proton hops back-and-forth quickly between water molecules. In systems more complex than bulk water, such as enzymes and ion channels, it is possible that water molecules, ions, and other protonatable groups (e.g., titratable amino acid residues) are “pre-organized” to facilitate concerted transfer.…”
Section: Introductionmentioning
confidence: 99%